Common National Curriculum Base: Perspectives of Environmental Education in Child Education (Research, Society and Development, 2022)
Common Nacional Curricular Base presents six fundamental axes within the scope of early childhood education: Living together, Participating, Playing, Exploring, Expressing, and Knowing yourself. In this sense, the present study analyzes the elements of the processes explicit in the document that are carried out in educational actions from the perspective of Environmental Education. Thus, this research aims to analyze the elements of the explicit processes in Common Nacional Curricular Base and their effectiveness in the educational actions of Environmental Education through innovative pedagogical practices that can encourage awareness and possibilities of interventions to meet the proposed axes and competencies by the document. The methodology is qualitative, documentary, and bibliographical. The analysis document was the Common Nacional Curricular Base. The discussions were based on Maria Carmen Barbosa (2020), Paulo Fochi (2016), Sauvé (2016) and Loureiro (2015). Its organization followed the assumptions of the Discursive Textual Analysis of Moraes and Galiazzi (2016). The results showed that in the analyzed document, the concept of Environmental Education is rarely mentioned in relation to the socio-environmental theme. To contemplate the propositions, present in the base, the teacher needs to involve the real problems and the performance of protection and improvement activities in a continuous and permanent way. It is allowing Education to be contemplated in ways that sensitize children to live and to themselves, as well as making evident the magnitude of approaches to Environmental Education in Early Childhood Education.